The effectiveness of training program based on lovaas’ program in developing children's autism spectrum disorder social skills - Najihah, Abd Wahid; Khaled Ahamd, Obiedat; Moath Amin, Nasaireh
Research problem: Autism spectrum disorders' children suffer from social skills problems. The aim of this study is to design a training program based on the Lovaas’ curriculum for development of Autism spectrum disorders' children social skills and to measure its effectiveness. To achieve the objective of this study, the researcher uses the descriptive approach and the semi-experimental approach based on the training program and measure of the social skills. The research population consists of autism spectrum disorders' children, ages 4 to 8 years, who were in the special education centers in Irbid governorate from the Hashemite Kingdom of Jordan for the year 2018/2019. The experimental and control groups were purposive sampling selected, which consisted of 30 children divided into two groups: experimental 15 and 15 control. Findings: The results of the descriptive analysis showed that a training program based on the Lovaas’ program was designed to develop social skills. The post-test results showed statistically significant differences between experimental and control groups at the level of a= 0.05, while the mean scores (29.8) indicated significantly for the experimental group of social skills in post-test. The delayed test results showed no statistically significant differences at the level of a= 0.05 for the experimental group. Conclusion: The researcher recommended the need to take advantages of the training program and the application program. One of the researcher's suggestions is to conduct a similar research on the Lovaas' approach for different age groups and different skills in the Hashemite Kingdom of Jordan.